Impacts of Pig Management and Husbandry Farmers Towards Classical Swine Fever Transmission in West Timor Indonesia (DAMPAK MANAJEMEN DAN CARA BETERNAK BABI TERHADAP PENULARAN PENYAKIT CHOLERA BABI DI TIMOR BARAT) - Bulu, Petrus Malo; Robertson, Ian; Geong, Maria (Jurnal Veteriner, 2015)
Classical swine fever (CSF) is a serious and highly infectious viral disease of domestic pigs and wildboar, which is caused by a single stranded RNA pestivirus. A cross sectional study was carried out onsmall-holder pig farmers in West Timor, in the province of East Nusa Tenggara, Indonesia. The objectiveof this study was to describe the management, husbandry and trading practices adopted by pig farmers inWest Timor. A questionnaire survey was administered to the owners of these pigs (n = 240) to gatherinformation from farmers in order to understand management and husbandry practices in the region. Theresults of the questionnaire highlighted the lack of implementation of biosecurity measures by smallholderfarms in West Timor, which has the potential to increase the risk of their pigs to CSF, as well as toother diseases.
Keywords: pig husbandry and management, classical swine fever (CSF), West Timor Indonesia